2013
DOI: 10.1002/app.39872
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of polyvinyl alcohol hydrogels with graphene oxide for potential dye removal

Abstract: Because of highly frozen macromolecule chains, polyvinyl alcohol (PVA) hydrogels have never been used for dye removal. This work focuses on improving the adsorption capacity of the PVA hydrogel by using amphiphilic graphene oxide to improve its macromolecular chain mobility in crystal domain and introduce new functional groups. To evaluate its effectiveness, crystal structure, swelling kinetics, and model dye methylene blue (MB) adsorption of the as-prepared PVA hybrid hydrogels were systematically investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…Ogawa et al (1992) reported that the first two peaks correspond to a hydrated form of CS. The diffraction pattern of PVA presented peaks at 2θ values of 12 • , 20 • , 23.4 • and 41 • ; these peaks corresponded to 350 diffraction planes of (100), (101), (200) and (111), respectively, according to Hyon et al (1975) and Li et al (2014). From the X-ray diffraction pattern located in the middle of Fig.2c), it can be observed that the peak associated with CS (at 10 • ) disappeared; in addition, the full width at half maximum (FWHM) of the peaks close to 20 • increased.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Ogawa et al (1992) reported that the first two peaks correspond to a hydrated form of CS. The diffraction pattern of PVA presented peaks at 2θ values of 12 • , 20 • , 23.4 • and 41 • ; these peaks corresponded to 350 diffraction planes of (100), (101), (200) and (111), respectively, according to Hyon et al (1975) and Li et al (2014). From the X-ray diffraction pattern located in the middle of Fig.2c), it can be observed that the peak associated with CS (at 10 • ) disappeared; in addition, the full width at half maximum (FWHM) of the peaks close to 20 • increased.…”
mentioning
confidence: 92%
“…Nevertheless, PVA is soluble in water. This property could be disadvantageous for some 10 applications; however, PVA has been widely used in applications such as articular cartilage and pancreas regeneration (Baker et al (2011);Paradossi (2013)), drug-eluting contact lenses (Carreira et al (2014)), sensors for biological variables (Tou et al (2014); Carmona et al (2015)) and even for capturing organic dyes and metallic ions (Li et al (2014); Hui et al (2015)). 15 Natural hydrogels such as collagen, gelatin, alginate, agarose and chitosan (CS) are very attractive and are commonly used for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the excellent prospects, G-gel still lacks superior chemical activity due to the deficiency of functional sites, which is not beneficial for its versatile application, typically the water purification [6][7][8][9][10][11]. It has been reported that the crosslinking of polymer with graphene produced functionalized G-gel, which is superior for water purification, such as poly(vinyl alcohol)/G-gel and poly(dopamine)/G-gel [12][13][14][15][16]. Aminecontaining conjugated polymers have been widely investigated as water purification agents during the last two decades [17].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Polyethylene glycol (PEG) and Poly(vinyl alcohol) (PVA) are biocompatible and biodegradable polymers widely used for the preparation of functional hydrogels in pharmaceutical industry. [13][14][15] PEG-based hydrogels can be prepared by ring-opening polymerization of ethylene oxide cyclic monomers, radiation crosslinking of PEG or free radical polymerization of PEG macromers, whereas PVA hydrogels can be prepared by the common freezing/thawing cycle without chemical crosslinking. 14,16,17 The functionalization of PEG and PVA hydrogels has been explored via a plethora of methods such as the Passerini three-component reaction, polyelectrolyte multilayer microencapsulation and microwave-assisted functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] PEG-based hydrogels can be prepared by ring-opening polymerization of ethylene oxide cyclic monomers, radiation crosslinking of PEG or free radical polymerization of PEG macromers, whereas PVA hydrogels can be prepared by the common freezing/thawing cycle without chemical crosslinking. 14,16,17 The functionalization of PEG and PVA hydrogels has been explored via a plethora of methods such as the Passerini three-component reaction, polyelectrolyte multilayer microencapsulation and microwave-assisted functionalization. [18][19][20] The heterogeneous network structures containing dense crosslinking regions are produced by chain polymerization of hydrogels.…”
Section: Introductionmentioning
confidence: 99%